Recent Progress in Doped g-C3N4 Photocatalyst for Solar Water Splitting: A Review - Yang, Yilong; Niu, Wantong; Dang, Liyun; Mao, Yanli; Wu, Junshu; Xu, Kaidong (Frontiers in Chemistry, 2022)
Graphitic carbon nitride (g-C3N4) photocatalysis for water splitting is harvested as a fascinating way for addressing the global energy crisis. At present, numerous research subject has been achieved to design and develop g-C3N4 photocatalysis and the photocatalytic system still suffers from the low efficiency that is far from practical applications. Here, there is an inspiring review on the latest progress of the doping strategies to modify g-C3N4 for enhancing the efficiency of photocatalytic water splitting, including non-metal doping, metal doping and molecular doping. Finally, the review concludes a summary and highlights some perspectives on the challenges and future research of g-C3N4 photocatalysts.